(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Information about new records and distribution of Pisolithus arrhizus (Scop.) Rauschert (Sclerodermataceae, Basidiomycota), a rare species, in Ukraine is presented. The fungus was found in Donetsk, Kharkiv, Kherson, Odesa and Poltava regions. Once it was recodred in Crimea on the territory of Karadag Nature reserve. In most cases this species was confined to sandy soils or pure sand. It is proposed to include this species into Red Data Book of Ukraine.